1989
DOI: 10.2527/jas1989.67112881x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Sire Scrotal Circumference to Offspring Reproduction and Growth

Abstract: Reproductive and growth data were obtained on 779 and 564 yearling beef heifers and bulls, respectively, that had sires with yearling scrotal circumference data at the San Juan Basin Research Center, Hesperus, CO. Partial regression coefficients of reproductive and growth traits on inbreeding (FXC) and age of the individual and adjusted scrotal circumference of sire (SCSI) were obtained. Growth and reproductive traits of heifers and growth and breeding soundness traits of bulls were analyzed. Separate analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 0 publications
4
38
2
1
Order By: Relevance
“…Similar estimates were found by Smith et al (1989) for a population that included Hereford and Angus cattle and by Morris et al (1993) for an Angus population (0.10 ± 0.17 and 0.15 ± 0.09, respectively). In contrast, several studies have reported higher estimates of heritability (from 0.27 ± 0.04 to 0.61 ± 0.17) for AP (e.g., MacNeil et al, 1984;Gregory et al, 1995;Morris et al, 2000).…”
Section: Heritability Estimatessupporting
confidence: 75%
See 3 more Smart Citations
“…Similar estimates were found by Smith et al (1989) for a population that included Hereford and Angus cattle and by Morris et al (1993) for an Angus population (0.10 ± 0.17 and 0.15 ± 0.09, respectively). In contrast, several studies have reported higher estimates of heritability (from 0.27 ± 0.04 to 0.61 ± 0.17) for AP (e.g., MacNeil et al, 1984;Gregory et al, 1995;Morris et al, 2000).…”
Section: Heritability Estimatessupporting
confidence: 75%
“…Similar estimates of heritability (0.01 ± 0.12 and 0.07 ± 0.09) were reported by Bourdon and Brinks (1982) and Smith et al (1989), respectively. Several authors, however, have found higher estimates of direct heritability for AFC.…”
Section: Heritability Estimatessupporting
confidence: 70%
See 2 more Smart Citations
“…Thus, 9500 samples were effectively used to estimate the parameters and highest posterior density (HPD) intervals. The Bayesian Output Analysis package (Smith, 2005) was used to calculate the mean, mode, median, s.d. and 95% HPD interval.…”
Section: Model and Parameter Estimationmentioning
confidence: 99%